Persepsi Mahasiswa Terhadap Program Kebijakan Merdeka Belajar Kampus Merdeka - Anwar, Rosyida Nurul (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine student perceptions of PG PAUD about MBKM. The method used is a descriptive quantitative method. Respondents were students of the PG PAUD study program as many as 28, consisting of 10 respondents from 2020/2021 class and 18 from the 2021/2022 class. The results showed that 96% knew and had heard of MBKM, but only 11% were aware of the program's policies, and only 4% did not know at all. 89% of students' interest in participating in MBKM is while the independent student exchange program and campus teaching are the activities most interested by students. Through MBKM, students can improve their hard and soft skills to realize quality education for all.